Emergency room - Cooney, Caroline B. (New York : Scholastic, 1994)
Volunteers Diane and Seth are eager to help save lives at a city hospital emergency room, but they are unprepared for the reality of what lies ahead.
Young Adult
Keywords: Hospitals -- Fiction; Volunteer workers in hospitals -- Fiction; Hospitals -- Fiction; Volunteer work -- Fiction